The Italianity of Noun + Noun compounds vs the influence of Anglo- American models - Godzich, Anna (Doświadczanie i wyrażanie włoskości: Aspekty językoznawcze i glottodydaktyczne, 2021)
The present article analyses the rules of present-day Italian wordformation with special focus on the influence of English lexems present in Italian Noun + Noun compounds. In some of Italian compunds the head element occurs on the right-hand side (the so-called right-hand head rule). That is often influenced by the presence of an English element. However lots of Noun + Noun Italian compounds with an English element exhibit the head-modifier structure (caldo killer, uomo sandwich, zucchine baby). The author decided to employ synchronic approach.